1999
DOI: 10.1046/j.1365-2567.1999.00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Human mannan‐binding lectin inhibits the infection of influenza A virus without complement

Abstract: Mannan-binding lectin (MBL) is a C-type serum lectin that is believed to play an important role in innate immunity. It is one of the collectin family, which is characterized by having a collagen-like sequence and a carbohydrate recognition domain. MBL can bind to sugar determinants of several micro-organisms, neutralize them and inhibit infection by complement activation through the lectin pathway and opsonization by collectin receptors. Bovine conglutinin and mouse MBL inhibit the infective and haemagglutinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
89
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 40 publications
6
89
1
Order By: Relevance
“…Also, opsonization of virions and infected cells by the deposition of C3b may lead to phagocytic uptake by leukocytes. Furthermore, interaction of complement components with virion surfaces on itself has been reported to be neutralizing for certain viruses (Ikeda et al, 1998;Kase et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Also, opsonization of virions and infected cells by the deposition of C3b may lead to phagocytic uptake by leukocytes. Furthermore, interaction of complement components with virion surfaces on itself has been reported to be neutralizing for certain viruses (Ikeda et al, 1998;Kase et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have focused on the direct anti-influenza virus activities of human MBL independent of complement activation and opsonization, and showed that human MBL had an ability to inhibit viral spreading from primary infected cells to noninfected cells, which was designated as viral growth inhibition (GI) activity, as well as inhibit viral hemagglutination and infectivity directly [19]. However, whether other animal serum collectins exert direct inhibitory effects against influenza A virus has not been definitely determined.…”
mentioning
confidence: 99%
“…Bovine MBL, rabbit MBL and human MBL were purified from each serum sample using mannan-agarose (SigmaAldrich Corp., St. Louis, MO, U.S.A.) as previously described [19][20][21]. BKg was purified from heat-inactivated (56°C, 30 min) bovine serum [29].…”
mentioning
confidence: 99%
See 2 more Smart Citations